Do the New Rural Pension Scheme promote the health status of chronic patients in old age? -Evidence from CHARLS 2018 in China - Qihong Liang; Yuxuan Chen; Zheng Zhang; Shengli An (BMC, 2023)
Abstract Background Many researchers have examined the impact of social insurance on health in elderly. However, in most cases, they have only demonstrated correlational results and have not been able to determine causal effects, possibly because confounding biases have not been fully addressed. In this study, we investigated the health effects of the New Rural Pension Scheme (NRPS) on the elderly (age≥60 years old) with chronic diseases in rural areas, and to explore the causal relationship and effects of NRPS and health status. Methods This paper used data from the 2018 China Health and Retirement Longitudinal Study (CHARLS) and applied Bayesian networks and fuzzy regression discontinuity design to conduct causal analysis. Bayesian networks were used to explore the causal directed acyclic graphs of factors related to NRPS and health status. Based on the results of Bayesian network, a fuzzy regression discontinuity design was employed to estimate the causal effect of NRPS on health status. Results Among rural elderly with chronic diseases, Bayesian network mapping of causal relationships among NRPS, health status and covariates showed that age was a common cause of NRPS receipt and satisfaction with health. The results of the fuzzy regression discontinuity analysis showed that the effect of receiving NRPS on the health status was positive, but there was no statistically significant difference concerning the interval estimates. The results of the subgroup analysis with chronic obstructive pulmonary disease (COPD) and asthma indicated that the effect of NRPS receipt on the health status of elderly people with COPD was positive. There was a statistically significant effect of receiving NRPS on self-rated health description ( $${β }_{1}=3.653,P=0.032$$ β 1 = 3.653 , P = 0.032 ) and health satisfaction ( $${β }_{1}=4.204,P=0.033$$ β 1 = 4.204 , P = 0.033 ) in COPD population and a statistically significant effect of receiving NRPS on health satisfaction in asthma population ( $${β }_{1}=9.844,P=0.008$$ β 1 = 9.844 , P = 0.008 ). Conclusion This paper has confirmed the contribution and positive causal effect of NRPS on health status in a subgroup of older adults with COPD and asthma, using the CHARLS database as evidence. Thus, Chinese government should increase the take-up rate of the NRPS to enhance their positive impact on health status of elderly people with chronic diseases in rural areas.